BUILDING AN IDEAL INDUSTRIAL RELATIONSHIP IN INDONESIA POST-DECISION OF THE CONSTITUTIONAL COURT - Nuridin, Nuridin; Hamzani, Achmad Irwan; Taufik, Mohammad; Khasanah, Nur (UNISSULA, 2022)
The terms of termination of employment due to gross misconduct by workers have been canceled. The ruler can no longer perform unilateral termination of employment. The determination of gross misconduct awaits the verdict of a court that has the force of law remains. The purpose of the study was to review the decision of the working relationship of gross misconduct after the decision of the Constitutional Court and to examine the working relationship between workers and the ideal ruler in the future. This study uses a philosophical approach, which is to examine the working relationships of workers and ideal rulers in the future. The results of this study showed that termination of employment among others because workers make severe mistakes that have the effect of not getting severance money and without any prior warning. The provision has been overturned by the Constitutional Court. Workers who commit gross misconduct must be proven first through criminal proceedings and there is a court ruling that has a fixed legal force. The pattern of worker and employer relationships is expected to create a mutually beneficial working relationship between the two parties in the future. The employment relationship of workers and employers is supposed to be a partnership relationship so that there is no discrimination, intimidation, and exploitation. Industrial relations ideally refers to Pancasila. With the source of Pancasila as a philosophical basis, and the 1945 Constitution all the rules of law governing Industrial Relations as its implementation. With this relationship, it is expected that the nuances of worker and employer relationships in the future can be harmonious, there is a positive syntactic relationship.